Preparation of polylactic acid / polypropylene blend via twin screw extruder - Mohd, Rudzaimi; Mohd Bijarimi, Mat Piah; Farah Hafidzah, Ahmad; Alhadadi, Waleed; M. Z. M., Noor; Azizan, Ramli; M., Norazmi (Universiti Malaysia Pahang, 2019)
In this work, poly (lactic acid) (PLA) and polypropylene (PP) were blended at various compositions in a twin screw extruder. The binary blend systems of PLA/PP were then characterised for thermal and morphological properties. It was found that the incorporation of PP in the PLA has resulted in the insignificant increment of melting and glass transition temperatures of the immiscible binary blend. The morphology of PLA/PP (60:40) shows the formation of voids due to the incompatibility of the blend system.